2022
DOI: 10.3389/fonc.2022.936088
|View full text |Cite
|
Sign up to set email alerts
|

Inter-fraction heart displacement during voluntary deep inspiration breath hold radiation therapy without visual feedback measured by daily CBCT

Abstract: Purpose/ObjectiveDeep Inspiration Breath Hold (DIBH) is now considered as the standard of care for many breast cancer patients. However, there are still uncertainties about the dose given to the heart, and it is unknown if patients may improve voluntary DIBH depth by gaining experience during treatment. In this study, we will examine the interfractional three-dimensional (3D) heart displacement throughout voluntary DIBH (vDIBH) radiotherapy by means of daily cone-beam computed tomography (CBCT).Material and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
3
3
Order By: Relevance
“…In particular, our measured IQRs were 4 mm in X, 2 mm in Y, and 2 mm in Z directions for all 250 fractions, whereas the largest distance reductions relative to the plans were 5 mm toward the left, 5 mm toward the superior, and 6 mm toward the anterior directions. Our IQRs were two to three times smaller than those reported in a previous study without visual feedback [ 10 ]. More specifically, their IQRs were 8.0 mm in X, 4.8 mm in Y, and 6.4 mm in Z directions for 225 fractions (15 cases each with 15 fractions), while the largest distance reductions were 21 mm toward the left, 9 mm toward the superior, and 18 mm toward the anterior directions.…”
Section: Discussioncontrasting
confidence: 93%
See 4 more Smart Citations
“…In particular, our measured IQRs were 4 mm in X, 2 mm in Y, and 2 mm in Z directions for all 250 fractions, whereas the largest distance reductions relative to the plans were 5 mm toward the left, 5 mm toward the superior, and 6 mm toward the anterior directions. Our IQRs were two to three times smaller than those reported in a previous study without visual feedback [ 10 ]. More specifically, their IQRs were 8.0 mm in X, 4.8 mm in Y, and 6.4 mm in Z directions for 225 fractions (15 cases each with 15 fractions), while the largest distance reductions were 21 mm toward the left, 9 mm toward the superior, and 18 mm toward the anterior directions.…”
Section: Discussioncontrasting
confidence: 93%
“…Dual registration using the daily CBCT and planning CT images showed that the medians of the changes in the chest wall to the heart distance among 25 fractions in each of the 10 cases ranged from -2 mm to 3 mm, -1 mm to 3 mm, and -2 mm to 1 mm in the X, Y, and Z directions, respectively. In addition, the reproducibility of the chest wall to the heart distance in our study is substantially better than previously reported two different studies where visual feedback was not employed [ 9 , 10 ]. In particular, our measured IQRs were 4 mm in X, 2 mm in Y, and 2 mm in Z directions for all 250 fractions, whereas the largest distance reductions relative to the plans were 5 mm toward the left, 5 mm toward the superior, and 6 mm toward the anterior directions.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations